2002
DOI: 10.3390/i3050475
|View full text |Cite
|
Sign up to set email alerts
|

Method of Moments of Coupled-Cluster Equations: Externally Corrected Approaches Employing Configuration Interaction Wave Functions

Abstract: Abstract:A new approach to the many-electron correlation problem, termed the method of moments of coupled-cluster equations (MMCC), is further developed and tested. The main idea of the MMCC theory is that of the noniterative energy corrections which, when added to the energies obtained in the standard coupled-cluster calculations, recover the exact (full configuration interaction) energy. The MMCC approximations require that a guess is provided for the electronic wave function of interest. The idea of using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 79 publications
(208 reference statements)
0
37
0
Order By: Relevance
“…We have recently introduced a new, nonstandard method of correcting the results of various CC calculations, termed the method of moments of coupled-cluster equations (MMCC) [7,[117][118][119][120][121][122][123]. The main idea of the MMCC formalism is that of the noniterative energy corrections which, when added to the energies obtained in approximate CC or equation-of-motion CC (EOMCC) [128][129][130] calculations, such as CCSD or EOMCCSD, recover the exact (full configuration interaction or full CI) energies of ground or excited states.…”
Section: (P)mentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently introduced a new, nonstandard method of correcting the results of various CC calculations, termed the method of moments of coupled-cluster equations (MMCC) [7,[117][118][119][120][121][122][123]. The main idea of the MMCC formalism is that of the noniterative energy corrections which, when added to the energies obtained in approximate CC or equation-of-motion CC (EOMCC) [128][129][130] calculations, such as CCSD or EOMCCSD, recover the exact (full configuration interaction or full CI) energies of ground or excited states.…”
Section: (P)mentioning
confidence: 99%
“…The main idea of the MMCC formalism is that of the noniterative energy corrections which, when added to the energies obtained in approximate CC or equation-of-motion CC (EOMCC) [128][129][130] calculations, such as CCSD or EOMCCSD, recover the exact (full configuration interaction or full CI) energies of ground or excited states. It has been demonstrated that the MMCC formalism allows us to renormalize the existing noniterative single-reference CC approximations, such as CCSD(T) [115], CCSD(TQ f ) [116], and CCSDT(Q f ) [116], so that they can correctly describe entire ground-state PESs in situations where the standard arguments based on MBPT, on which the CCSD(T), CCSD(TQ f ), and similar approximations are based, completely fail [7,26,[117][118][119][120][121][131][132][133] (cf., also, Ref. 134 for a rederivation of the renormalized CCSD(T) expressions, published one year earlier in Refs.…”
Section: (P)mentioning
confidence: 99%
See 3 more Smart Citations